Analisis Kadar Serat dan Uji Organoleptik Sempol dengan Substitusi Tepung Sukun (Artocarpus altilis) - Puspikasari, Putri; Akbar, Abdul Azis (Universitas Airlangga, 2024)
Background: Breadfruit production in Indonesia is very abundant, in the first quarter the production of breadfruit in Indonesia reached 33,382 tons. Breadfruit fruit can be processed into breadfruit flour to be used as material for making breadfruit flour formulation sempol (0%, 25%, 40%, 55%). In 100 grams of breadfruit flour contains high fiber as much as 3.7 grams of fiber. Fiber is able to slow down the absorption of glucose in the stomach to prevent the occurrence of diabetes mellitus. Objectives: This study aims to analyze the fiber content and organoleptic test of sempol by substitution of breadfruit flour (Artocarpus altilis). Methods: This research is a type of quantitative research with a quasi-experimental research design. The research sample consisted of 35 panelists taken by purposive sampling. Acceptance data were obtained from the organoleptic test form and analyzed using the Kruskal Walis method followed by the Man Whitney method. Fiber content data was obtained from the results of the gravimetric test laboratory and analyzed using the One Way Anova method followed by the Duncan method. Results: The results showed that the fiber content in sempol was significantly different (p=0.05). The results of the sempol organoleptic test showed significant differences in the parameters of color (p=0.000), aroma (p=0.001), and taste (p=0.008). In the organoleptic test for texture parameters there was no significant difference (p=0.149). Conclusions: In the gravimetric test the crude fiber content showed an increase in each sample treatment with the highest yield of crude fiber sample X3 of 2.14%. The results of the organoleptic test for color and aroma parameters were highest in sample X0 (control) with a score of 3.86 and 3.69 respectively, in the parameters of taste and texture the highest results were in sample X1 (substitution of breadfruit flour 25%) each score of 3.49 and 3.31.